2016
DOI: 10.1097/mbc.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Central venous access device insertion and perioperative management of patients with severe haemophilia A

Abstract: Central venous access device (CVAD) insertion is one of the most common procedures performed on paediatric haemophilia patients. There are no clear guidelines outlining the optimal dosing schedule of factor VIII (FVIII) and duration of treatment required to achieve adequate haemostasis during and after surgery. In this article, we describe the experience at McMaster Children's Hospital using FVIII replacement therapy in 15 children with severe haemophilia A during the course of 7 years. This is a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, there is a limited number of published studies reporting the management of CVAD insertions in children. The experience of the McMaster Children's Hospital showed that the dose of factor administration had gradually decreased over time and that the total perioperative dose was 912.2 IU/kg [ 15 ]. Minna et al [ 16 ] proposed that less than 4 days may be as safe and effective as longer replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a limited number of published studies reporting the management of CVAD insertions in children. The experience of the McMaster Children's Hospital showed that the dose of factor administration had gradually decreased over time and that the total perioperative dose was 912.2 IU/kg [ 15 ]. Minna et al [ 16 ] proposed that less than 4 days may be as safe and effective as longer replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased need to find cost‐effective CFC replacement treatment for CVAD surgery without compromising the safety. Fonseca et al recently reported the experience at McMaster Children's Hospital to find an optimal haemostatic coverage during CVAD surgery 5 . They concluded that decreased FVIII dosage resulted in a similar successful outcome with no bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of bleeding associated with CVAD surgery has been reported to vary between 7% and 22% according to previous studies 6 . Little knowledge on optimal replacement therapy for CVAD insertion is available beyond single centre experiences 5,6 . As intensive treatment is a risk factor for antibody formation, 4 many physicians who treat for 5 days or longer try to minimize the risk by postponing the time of insertion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given its rarity, reports from collaborative European efforts such as the European Acquired Haemophilia registry (EACH-2)3,[6][7][8] and the GTH (Acquired Haemophilia Working Group of the German, Austrian and Swiss Thrombosis and Hemostasis Society) registry9,10 have provided key insights. Toronto ' s St. Michael ' s Hospital (SMH) is the largest Canadian adult haemophilia treatment centre (HTC); we reviewed the clinical characteristics of AHA patients treated at SMH from 1990 to 2016.…”
mentioning
confidence: 99%